(Benz)Imidazole‐Directed Cobalt(III)‐Catalyzed C–H Activation of Arenes: A Facile Strategy to Access Polyheteroarenes by Oxidative Annulation. Issue 40 (17th October 2018) - Dutta, Pratip Kumar; Sen, Subhabrata
Abstract : A facile cobalt(III) catalyzed C–H activation of arenes with substituted (benz)imidazoles as directing groups (DG) is reported. The strategy was utilized for the synthesis of polyheteroarenes when appropriate substrates were treated with diarylacetylenes as the coupling partner. The desired compounds were synthesized in moderate to excellent yield. A putative reaction mechanism is proposed. The final compounds revealed photoluminescence properties. Abstract : Cobalt catalyzed (benz)imidazole‐directed C–H activation of arenes provides access to polyheteroarenes by oxidative annulation.